2020
DOI: 10.5009/gnl19079
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Metachronous Gastric Cancer after the Endoscopic Resection of Gastric Epithelial Neoplasia: Roles of <i>Helicobacter pylori</i> Eradication and Aspirin

Abstract: Whether Helicobacter pylori eradication actually reduces the risk of metachronous gastric cancer (MGC) development remains a controversial question. In this review, we addressed this topic by reviewing the results of clinical investigations and molecular pathological analyses of the roles of H. pylori eradication and aspirin administration in the prevention of MGC. In regard to the clinical studies, the results of metaanalyses and randomized control trials differ from those of retrospective studies: the former… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 92 publications
0
6
1
Order By: Relevance
“…In contrast with previous studies [ 18 , 19 , 20 ], the associations of statin, aspirin, and COX2 inhibitor use with a decreased risk of metachronous gastric cancer did not reach statistical significance in this study. We suggest two reasons for this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast with previous studies [ 18 , 19 , 20 ], the associations of statin, aspirin, and COX2 inhibitor use with a decreased risk of metachronous gastric cancer did not reach statistical significance in this study. We suggest two reasons for this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, Ihara et al found that the incidence of intestinal-type gastric cancer was higher in aspirin users than in non-users (0.14%; p = 0.004) [ 18 ]. The molecular basis of the effects of H. pylori eradication and aspirin use on the risk of MGC have also been explored [ 15 ]. In another meta-analysis, aspirin use was associated with a reduced incidence of several cancers (odds ratio 0.62; 95% CI, 0.55–0.70; p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of H. pylori infection, which has a proven protective effect on metachronous recurrence, it is necessary to change the molecule and find the point of no return for infected chronic atrophic gastritis and intestinal metaplasia, compared to a single treatment. It has been suggested that aspirin and nonsteroidal anti-inflammatory drugs have additional effects [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the published clinical studies, Hp eradication and aspirin use are likely to stop the development of metachronous gastric cancer (MGC). Meta-analyses and RCTs show that Hp eradication reduces the risk of MGC development in patients who were followed up for a long term after the eradication (≥5 years) [ 119 ].…”
Section: Prevention Of Gastric Cancermentioning
confidence: 99%